ANALISA EFISIENSI WATER TUBE BOILER TAKUMA N750 DI PABRIK KELAPA SAWIT - Rahmadhani, Novia; Youfa, Rita (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2021)
This study evaluates the efficiency of the Takuma N750 water tube Boiler at a palm oil mill, which has a maximum evaporation capacity of 27 tons per hour. Boiler efficiency is crucial for converting thermal energy from fuel into steam, with operational data showing significant efficiency variations. The average efficiency was 54.34%, substantially below the target of 80%, with the highest recorded efficiency at 60.4% and the lowest at 51.08%. The analysis revealed an inverse relationship between excess air and Boiler efficiency; as excess air increases, efficiency decreases. For instance, with 139.22% excess air, efficiency dropped to 56.36%, compared to 60.4% with 123.44% excess air. The study concludes that optimizing excess air levels is essential for improving Boiler efficiency, recommending adjustments to combustion parameters and excess air control to enhance performance and reduce operational costs. This research offers insights into better Boiler operation and energy management in palm oil mills.